Coding and Coherent Decoding techniques for Continuous Single Slope Cyclic Shift Chirp Signal - Lerson Kirasamuthranon; Paramote Wardkein; Jeerasuda Koseeyaporn (Radioengineering, 2023)
Chirp signals are currently widely used in broadband and spread spectrum communications due to their advantageous features, such as immunity to fading noise, low power consumption, consistent long-range transmission, and constant bandwidth. As a result, they are applied at the physical layer of the Internet-of-Things (IoT). This study proposes two techniques for encoding and decoding 4-cyclic shift chirp symbols, based on addition and subtraction operations. The proposed techniques have simple structures that can be easily implemented using analog circuits. The proposed encoding techniques reveal obviously the relationship between cyclic-shift chirp symbols and pulse modulating signals (PWM, PPM, and PAM), which is rarely discussed in prior research. Moreover, the circuit for encoding and decoding of the proposed technique is implemented by discrete commercial devices at low frequency
Keywords: Radar Systems and Signal Processing; Underwater Vehicles and Communication Systems; Advanced SAR Imaging Techniques